Comparitive study on culture economics of Litopenaus vannamei between summer and winter seasons along Tamilnadu coastal areas - N, Inayathullah; K, Srilaxmi; P, Vijayanand (International Journal of Aquatic Research and Environmental Studies, 2022)
Shrimp has emerged as a significant consumable product in world seafood production. Many Asian countries such as India, Indonesia, Taiwan, and Thailand have appeared as worldwide leaders in shrimp production. Shrimp aquaculture has played a vital role by providing an alternative source of income for shrimp farmers along the coastal districts of Tamil Nadu and is considered a sunrise sector supporting economic development.In the present study, during summer culture the maximum stocking density was observed at Pattukottai (80/m²), followed by the Tuticorin region (70/m²). In winter culture, the maximum stocking density was recorded at Pattukottai and Tuticorin district (60/m²). In summer culture, the maximum production cost was recorded in the Tuticorin region (272 Rs), followed by the Ramnad region (237 Rs). The minimum production cost was recorded in the Nagapattinam region (201 Rs), followed by the Ponneri region (206 Rs). During summer culture, the maximum profit was obtained from the Ponneri region (61%), followed by the Nagapattinam region (57%). The minimum profit was recorded in the Tuticorin region (22%). In winter culture, the maximum profit was recorded in the Nagapattinam region (56%), followed by the Ponneri region (55%). However, the Pudukottai and Pattukottai regions recorded the same profit in both culture periods.
Keywords: Aquaculture; Economic development; Stock density